2021
DOI: 10.3389/fnagi.2020.580001
|View full text |Cite
|
Sign up to set email alerts
|

Propionate and Alzheimer’s Disease

Abstract: Propionate, a short-chain fatty acid, serves important roles in the human body. However, our review of the current literature suggests that under certain conditions, excess levels of propionate may play a role in Alzheimer’s disease (AD). The cause of the excessive levels of propionate may be related to the Bacteroidetes phylum, which are the primary producers of propionate in the human gut. Studies have shown that the relative abundance of the Bacteroidetes phylum is significantly increased in older adults. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 132 publications
(146 reference statements)
2
24
0
Order By: Relevance
“…Skin microbiota members, specifically Actinobacteria , are known to be propionate producers. In addition, saliva, fecal and hippocampus propionate levels have been found to increase significantly in Alzheimer’s disease patients [30]. Our results also suggest a potential association between the increase in propionate biosynthesis by skin microbiota and CI stages in PD.…”
Section: Discussionsupporting
confidence: 63%
“…Skin microbiota members, specifically Actinobacteria , are known to be propionate producers. In addition, saliva, fecal and hippocampus propionate levels have been found to increase significantly in Alzheimer’s disease patients [30]. Our results also suggest a potential association between the increase in propionate biosynthesis by skin microbiota and CI stages in PD.…”
Section: Discussionsupporting
confidence: 63%
“…Species within these genera metabolise lactate to the SCFAs propionate and acetate while producing hydrogen [ 136 ]. Whilst propionate has been hypothesised to have antidepressant effects, excess propionate has been associated with increased depressive-like behaviours in animal studies [ 137 ] and elevated levels of propionate have been reported in Alzheimer’s disease [ 138 ]. In addition, it has been hypothesised that a by-product of lactate metabolism—hydrogen—may also influence host physiology [ 130 , 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skin microbiota members, specifically Actinobacteria , are known to be propionate producers. In addition, saliva, fecal, and hippocampus propionate levels have been found to increase significantly in Alzheimer’s disease patients ( 23 ). Our results also suggest a potential association between the increase in propionate biosynthesis by skin microbiota and CI stages in PD.…”
Section: Discussionmentioning
confidence: 99%